The influence of financial literacy and psychological factors on money market mutual fund investment decisions - Muhammad Rayhan Indrastoto; Ratna Juwita (Journal of Applied Sciences in Accounting, Finance, and Tax, 2023)
Indonesia has experienced economic growth after the Covid-19 pandemic, which was accompanied by an increase in the number of first-time investors, especially the millennial and z generations. However, the lack of financial and psychological literacy of each investor, especially beginners who are not mature enough, will affect investment decisions that are not optimal. This study aims to examine the effect of financial literacy and psychological factors on money market mutual fund investment decisions. This research is a type of quantitative research. Methods of data collection by distributing questionnaires to 395 respondents who meet the criteria. The method used is Structural Equation Model - Partial Least Square. From the results of the study it was found that the T test on the independent variable Financial Literacy was 3,455 with a significance of 0.001, which means it has a significant effect on investment decisions, Emotion is 1,487 with a significance of 0.137, which means it does not have a significant effect on investment decisions, Social Interaction is 0.890 with a significance of 0.374, which means it is not significant effect on investment decisions, Considering The Past of 2.769 with a significance of 0.006, which means a significant effect on investment decisions. It is hoped that this research will provide insight to respondents that investment decisions can be measured using the level of financial literacy and psychological factors such as emotions, social interaction and considering the past.